Localized Corrosion: Passive Film Breakdown vs. Pit Growth Stability: Part III. A Unifying Set of Principal Parameters and Criteria for Pit Stabilization and Salt Film Formation. Issue 11 (1st January 2018) - Li, Tianshu; Scully, J. R.; Frankel, G. S.
Abstract : The framework for pit stability established in Part II of this series is elaborated upon and expanded. The maximum pit dissolution current density, i diff, max, which depends on temperature and maximum potential at the pit surface in a given pit environment, is proposed and compared with the diffusion current density to determine the conditions for pit stability and salt film formation. For an open pit, the criterion for pit stability is that i diss, max must be greater than or equal to the critical diffusion current density required for maintaining a critical local environment for active dissolution, i diff, crit . The critical condition of i diss, max = i diff, crit is associated with three parameters that must be exceeded for stabilization of an open pit: critical temperature T crit, critical potential E crit and critical pit depth r crit . Analogously, the criterion for salt film formation is i diss, max must further exceed the diffusion-limited current density i lim, and three parameters associated with salt film formation are: saturation temperature T sat, saturation potential E sat and saturation pit depth r sat . Unifying criteria for control of pit growth by charge transfer or diffusion are proposed, which provide interrelationships for all principle parameters. The pit stability criteria for covered pits, such as metastable pits, are also described.